4x + 3y = 1y = 2x + 8
Take the first part:
4x + 3y = 1y
4x = 1y - 3y
4x = -2y
x = -y/2
Substitute x in second part:
1y = 2x + 8
1y = -2y/2 + 8
1y = -1y + 8
2y = 8
y = 4
Substitute y into either part:
1y = 2x + 8
1(4) = 2x + 8
4 - 8 = 2x
-4 = 2x
x = -2
Therefore:
x = -2
y = 4
Chat with our AI personalities
2x+1 = 9 2x = 9-1 2x = 8 x = 4
3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8
8x = 2x + 15 6x = 15 x = 15/6 = 2.5
2x + 12 y =36subtract 2x from both sides12y = 36 - 2xdivide both sides by 12y = (36 - 2x)/12
-2x+14=20 -2x=20-14 -2x=6 -2x/-2=6/-2 x=-3